Genotype and biotype of invasive Anopheles stephensi in Mannar Island of Sri Lanka - Surendran, S.N.; Sivabalakrishnan, K.; Gajapathy, K.; Arthiyan, S.; Jayadas, T.T.P.; Karvannan, K.; Raveendran, S.; Karunaratne, S.H.P.P.; Ramasamy, R. (University of Jaffna, 2018)
Anopheles stephensi, the major vector of urban malaria in India, was recently detected for the first time in Sri Lanka in Mannar Island on the northwestern coast. Since there are different biotypes of An. stephensi with different vector capacities in India, a study was undertaken to further characterise the genotype and biotype of An. stephensi in Mannar Island.
Keywords: anopheles stephensi; biotype; cox1; cytb; malaria vector; mannar Island; Spiracular index; sri lanka; ITS2